Genetic testing for CHD risk: fact or fiction? - Humphries, Steve (Henry Stewart Talks, 2008)
Family history is a strong independent risk factor for early CHD, Criteria for useful CHD-Risk DNA tests, Analytical validity, Clinical validity, Risk estimates for genetic effects, Clinical utility, Risk score methods, CRP: origin, clearance and function, Is it likely that genotype will predict risk over and above trait measure?, CDNK2A genotype and prospective CHD risk in NPHSII, Six GWAS SNPs for risk prediction, Will genotypes of modest risk be useful in combination, Risk genotype frequency distribution and associated odds ratios, Genetic tests for CHD: using lipid gene SNPs, Can we use DNA information to optimize risk stratification, Measures of predictive performance, Use genetic information to stratify intermediate risk, Model clinical utility of adding CDKN2A risk information, Risk score distribution, CRFs and genotype, ELSI: risk perception and behaviour change, Ethical, legal and social impact, Perception of risk information, Smoking cessation motivation by DNA risk: design and results, DNA tests and CHD risk stratification: are we ready now?
Archived at 2021/02/25